2010
DOI: 10.1016/j.jalz.2009.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Alzheimer's disease diagnosis via high‐resolution blood gene expression

Abstract: This study provides proof-of-concept that whole-blood profiling can generate an AD-associated classification signature via the specific relative expression of biologically relevant RNAs. Such a signature will need to be validated with extended patient cohorts, and evaluated to learn whether it can differentiate AD from others types of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 66 publications
3
59
0
Order By: Relevance
“…We and others have previously shown that disease biomarkers to classify AD with dementia from cognitively healthy individuals are present in blood [16,23,35] and an algorithm based on the gene expression of a selected set of genes can be used to identify those with an AD dementia [34][35][36]. We have now further extended these findings to also include AD in the pre-dementia stage of the disease.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…We and others have previously shown that disease biomarkers to classify AD with dementia from cognitively healthy individuals are present in blood [16,23,35] and an algorithm based on the gene expression of a selected set of genes can be used to identify those with an AD dementia [34][35][36]. We have now further extended these findings to also include AD in the pre-dementia stage of the disease.…”
Section: Discussionmentioning
confidence: 80%
“…Several independent studies have indicated that a blood-based test could be used for diagnostic profiling in neurological diseases [16][17][18][19][20][21][22][23][24]. Lönneborg [21] summarized in 2008 that of several studies that investigated plasma A␤ levels in AD; one study showed an increase in A␤ levels [25] and the majority of studies found no significant differences between AD and controls [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Fehlbaum-Beurdeley et al [31] verified 133 genes in blood cells whose expression pattern may distinguish AD patients from controls. These genes were involved in five major pathways occurring in macrophages and lymphocytes, such as to the transforming growth factor-beta signaling, oxidative stress, cytoskeletal organization, inflammatory and immune responses, lipid-raft, cholesterol homeostasis and the ubiquitin proteasome system.…”
Section: Discussionmentioning
confidence: 99%
“…"signatures" in blood, detectable using microarrays [51,52]. Notably, melanoma also has a characteristic signature in blood due to reduced interferon signaling (which is not necessarily melanoma-specific, however) [53].…”
Section: Skinomics In Our Futurementioning
confidence: 99%